677 Evaluation of anti-PD1 efficacy in germ-free and antibiotic-treated SPF mice bearing MC38 tumors. (9th November 2020) - Jin, Ying; Liang, Xue; Zhang, Frieda; Mu, Guangmao; Zhou, Wei; An, Annie; Ouyang, Marvin; Li, Cai; Liaw, Andy; Li, Henry; Ouyang, Davy
Abstract : Background: Increasing evidence has indicated the important role of gut microbes in mediating normal and pathologic immune responses to cancer in both patients and animal models. There is growing effort in modulating microbiota composition to improve the outcome of cancer immunotherapy. To investigate the immunomodulatory roles of microbiota-based therapeutics preclinically, germ-free (GF) mice are often used because they are free of microorganisms. However, logistic challenges and inherited physiological deficits in GF mice are also generally acknowledged. Alternative approach of depleting gut microbiota in using specific pathogen-free (SPF) mice with broad-spectrum antibiotics has also been adopted. Potential challenges with this approach are possible acquisition of antibiotic-resistant bacteria and potential expansion of fungi. Here we report on the efficacy assessment of anti-PD-1 mAb on MC38 syngeneic tumors in both GF mice and antibiotic-treated SPF mice. Methods: C57BL/6 mice were inoculated subcutaneously with MC38 tumor cells. In the GF study, GF mice (Taconic, provided by Cyagen) were housed in germ-free isolators at a Cyagen facility, and a cohort of SPF mice (Taconic) were used as controls. Both GF and SPF mice were randomized for isotype or anti-PD-1 mAb (mDX400) treatment when the tumors were established (80–120 mm 3 ) and were continuously monitored for tumor growth over time. In the antibiotic treatment study, different antibiotic regimens were administered to SPF mice (Lingchang) in drinking water starting 2 weeks prior to MC38 tumor inoculation and continued throughout the study. Mice were treated with vehicle control or anti-PD-1 mAb (RMP1-14; CrownVivo™). Results: Tumor growth is significantly faster in GF than SPF mice, and mDX400 slowed the tumor growth rate in both GF and SPF mice. The tumors achieved complete regressions on 4 out of 10 GF mice as compared to 6 out of 10 SPF mice, yet the difference of mDX400 efficacy in GF vs SPF mice did not reach statistical significance. In antibiotic-treated SPF mice, none of the antibiotic regimens showed significant impact on MC38 tumor growth nor anti-PD-1 efficacy in SPF mice, which was contrary to most reported data. Immune profiling on tumor infiltrating lymphocytes in these mice and microbiota analysis by 16S rRNA gene amplicon sequencing are ongoing and the data will be presented at the meeting. Conclusions: We have observed faster tumor growth in GF mice, however, the efficacy of anti-PD-1 antibody is not impacted by GF condition or treatment with broad-spectrum antibiotics. These results are different from previously published work, indicating high variability in preclinical models. Ongoing analysis with antibiotic-treated mice will provide further insight. Ethics Approval: Animal experiments were conducted in accordance with animal welfare law, approved by local authorities, and in accordance with the ethical guidelines of CrownBio (Taicang).